Kerjasama Keamanan Maritim Indonesia-Australia dalam Menangani IUU Fishing di Laut Arafura - Ekaputra, Muhammad Edrian; Susiatiningsih, Hermini; Hanura, Marten (Journal of International Relations, 2018)
IUU (illegal, unreported, unregulated) fishing was deemed by Indonesia as a crime thatinflicted many loss. In Indonesia, IUU fishing mostly occured at Arafura Sea whereAustralian sea territory were partially included. The mentioned problems in this researchare why Indonesia and Australia establish a cooperation to deter IUU fishing at Arafurasea and the affects. The purpose of this research is to explain and analyse the cooperationthat undertaken by Indonesia and Australia to deter IUU fishing at Arafura Sea. For thosepurposes, this research using the liberalism theory, cooperation concept, maritime securityconcept and transnational crime concept as a tool of analysis. This research is conductedby using the qualitative research method with explanative research type through interviewsand literature studies. The cooperation between Indonesia and Australia to deter IUUfishing at Arafura Sea were conducted through bilateral an multilateral efforts. For bothstates, particulary Indonesia, the cooperation are the part of their efforts to create amaritime security with the protection of economic and reliability sector of respective statesas the ultimate goal.